Does the Judiciary Support Legal Certainty? An Indonesian Perspective - Aditya, Zaka Firma (Frontiers in Law, 2023)
Many legal thinkers have tried to interpret what and how the principle of legal certainty enforced. In both civil and common law traditions, legal certainty is considered a value and the basis for the legality of public authorities’ legislative and administrative actions. The meaning of these two views, both Civil law and Common law, is that legal certainty is the embodiment of the principle of legal legality or in other words, legal certainty related to law enforcement itself. Interestingly, legal certainty begins with the legal uncertainty created by the institutions that form it. The judge’s role in interpreting, translating and finding the law is crucial so that there is no legal vacuum due to the malfunction of the rule of law. This paper will discuss how the Indonesian judiciary supports legal certainty. The research method used is juridical normative with conceptual, and case approaches. The results of this study indicate that the Indonesian judiciary supports legal certainty through legal interpretation and legal findings made by judges. This legal interpretation and legal findings’ primary purpose is to fill the legal gap left by laws that are multiple interpretations and ambiguous.